(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the implementation of character education at the University of Nias. The type of research used is qualitative descriptive. The subjects of this study consist of lecturers (3 people) and students (5 people) at the University of Nias. Techniques to collect data through interviewing subjects, namely lecturers and students by providing several questions relevant to our mini research about the character of students. The data analysis technique in this study is qualitative analysis with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that Nias University students have a character that plays a very important role in shaping students who are not only superior in academics, but also emotionally and socially mature. By instilling an attitude of respecting differences, empathy, and having good self-control, students can create an inclusive and productive campus environment. In addition, the application of character values such as integrity, discipline, and responsibility strongly supports students’ personal development, so that they are ready to face future challenges